The 1980 Aparejo Glacier catastrophic detachment: new insights and current status - Felipe Ugalde; Gino Casassa; Gino Casassa; Cedomir Marangunic; Francisco Fernandoy; Jorge Carrasco; Franco Buglio (Frontiers in Water, 2024)
The catastrophic detachment of Aparejo Glacier (one of the three known cases in the Andes) took place on 1 March 1980 and resulted in the removal of an ice volume initially estimated to be 7.2 Mm3, which originally was 1.0 km long and covered an area of 0.2 km2. The event caused the sudden mobilization of the sliding mass 3.7 km down valley at an estimated speed of 110 km/h, causing remarkable geomorphological changes, including the obliteration of most of the glacier. 40 years after the event, we analyze new evidence: 3 ground surveys carried out in 2015 and 2016; DEMs and glacier outlines compiled from orthorectified aerial imagery pre-and post-event; GNSS data; Ground Penetrating Radar (GPR) data; a terrestrial LiDAR scan survey of 2020, together with detailed interviews with 2 direct witnesses of the event, terrestrial and helicopter-borne photographs acquired 12 days after the sudden detachment. The combined interpretation of these new data, allow us to make a more precise estimation of the pre-detachment glacier volume, 12.9 ± 0.6 × 106 m3 and the detached ice volume of 11.7 ± 0.6 × 106 m3 (90% of the total volume of the glacier). We also show that in the 40-year period Aparejo Glacier has recovered 12.4% of the original glacier volume, with a mean ice thickness of 19.5 m and a maximum of 40 m according to GPR data, being preserved within the same basin as the detached glacier. In recent years, the glacier has shown a mean elevation change of −3.7 ± 1.2 m during the 2015–2020 period, with maximum thinning values greater than 8 m, which are probably caused by enhanced ablation due to climate warming and reduced precipitation during the current megadrought which started in 2010 and has lasted more than 1 decade. We conclude that under the projected scenarios of climate warming and reduced precipitation for central Chile, the risk associated to a new detachment of Aparejo Glacier is unlikely.